Current Status of Ethosomes and Elastic Liposomes in Dermal and Transdermal Drug Delivery - Ita, Kevin (Current Pharmaceutical Design, 2016)
It is still not clear whether intact lipid vesicles can cross the human skin. Some reports in the literature indicate that transfersomes® can cross the skin. Other reports suggest that intact liposomes cannot cross the skin. Of course, the composition of the various formulations has to be taken into consideration before making such assertions. The present review examines the use of vesicles- elastic liposomes and ethosomes- for transdermal drug delivery. Liposomes are micro- or nano-structures formed from a bilayer of lipid surrounding an aqueous core. Elastic liposomes differ from conventional liposomes because they contain edge activators (surfactants) which impart elasticity and deformability. Ethosomes are efficient in facilitating percutaneous drug penetration. They are structurally similar to conventional liposomes in the sense that they are prepared from phospholipids but different because they contain a high concentration of ethanol. Both elastic liposomes and ethosomes are increasingly being used for delivering low and high molecular weight drugs. In this review, several reports are presented showing the usefulness of these vesicles and mechanistic insight sought as to why they may be effective in certain cases.
Keywords: vesicles